TPU (thermoplastic polyurethane) elastic master batch, elastic adhesive interlining and production process of TPU elastic master batch

By using the TPU elastic masterbatch production process, combined with functionally improved fillers and modified nano-titanium oxide agents, the problems of poor air permeability and water repellency of TPU hot melt adhesive film materials have been solved, achieving coordinated improvement in the performance of elastic adhesive liner and enhanced salt corrosion resistance.

CN121086282AActive Publication Date: 2025-12-09SHISHI JIANAN HOT MELT ADHESIVE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511648182.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-12
Publication Date
2025-12-09
Estimated Expiration
2045-11-12

AI Technical Summary

Technical Problem

Existing TPU hot melt adhesive film materials, when optimized for elasticity, suffer from poor air permeability and water repellency, as well as insufficient salt corrosion resistance, which limits the product's efficiency.

Method used

The TPU elastic masterbatch production process involves melt blending and extrusion granulation of functionally improved fillers, modified nano-titanium oxide agents, coupling agent KH560, and calcium stearate, followed by melt-blowing to obtain an elastic adhesive liner. This optimizes elasticity, breathability, and water repellency, and improves salt corrosion resistance.

Benefits of technology

The elastic properties, breathability, and water repellency of the elastic adhesive liner were significantly improved, and the product's salt corrosion resistance was enhanced, achieving a coordinated improvement in performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of functional master batches and adhesive interlinings, in particular to TPU elastic master batches, an elastic adhesive interlining and a production process of the TPU elastic master batches, and the production process of the TPU elastic master batches comprises the following steps: weighing the following raw materials in parts by weight: TPU, a filling agent based on functional improvement, a modified nano titanium oxide agent, a coupling agent KH560 and calcium stearate; the raw materials are subjected to melt blending and extrusion granulation, the rotating speed of an extruder is 150 r / min, the extrusion temperature is 200 DEG C, and the TPU elastic master batch is obtained. According to the TPU elastic master batch, TPU is adopted as a matrix, a filling agent based on functional improvement and a modified nano titanium oxide agent are matched to serve as functional auxiliaries, a coupling agent KH560 and calcium stearate are added for blending, and melt blending and extrusion granulation are carried out; the elastic adhesive interlining prepared from the TPU elastic master batch has the advantages that the elastic property, the air permeability and the water repellency are harmoniously improved, and the salt corrosion resistance stability effect of the product is obvious.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of functional master batch and adhesive lining, in particular to a TPU elastic master batch, an elastic adhesive lining and a production process thereof. BACKGROUND

[0002] The layer structure of spandex cloth is that hot melt adhesive films are compounded on both sides of a spandex woven base cloth, the elasticity of the spandex intermediate cloth is used to compensate for the insufficient elasticity of the hot melt adhesive film itself, the elastic performance is enhanced, and in use, the hot melt adhesive films on both sides are hot melt bonded with the face cloth and the lining cloth of the clothes, and are mainly applied to elastic parts such as underwear and underpants.

[0003] Since the specific gravity of the spandex intermediate cloth is large, it is a common practice in the art to replace the spandex intermediate cloth with melt-blown TPU while retaining the hot melt adhesive films on both sides, and in order to optimize the elastic performance of the product, the existing TPU hot melt adhesive film material has poor air permeability and water repellency, it is difficult to achieve coordinated improvement in performance, and the product has poor salt corrosion stability, which limits the use efficiency of the product. Therefore, it is necessary to develop an elastic adhesive lining and a functional master batch thereof. SUMMARY

[0004] In view of the defects of the prior art, the purpose of the present application is to provide a TPU elastic master batch, an elastic adhesive lining and a production process thereof to solve the problems raised in the background art.

[0005] The technical problem solved by the present application adopts the following technical solution: The present application provides a production process of a functional master batch, comprising the following steps: Step one, weigh the raw materials according to the weight parts: 55-60 parts of TPU, 5-8 parts of a functional improvement-based filling agent, 3-5 parts of a modified nano-titanium oxide agent, 2-4 parts of a coupling agent KH560, and 3-5 parts of calcium stearate; Step two, melt blend and extrude the above raw materials to obtain TPU elastic master batch, the rotation speed of the extruder is 150 r / min, and the extrusion temperature is 200 DEG C.

[0006] Preferably, the preparation method of the functional improvement-based filling agent is: S01: calcium carbonate is added to a 5-8% sodium dodecylbenzenesulfonate solution according to a weight ratio of 3:5, stirred uniformly, and a calcium carbonate solution is obtained; 4-7 parts of glass beads, 2-3 parts of carboxymethyl cellulose sodium, and 5-8 parts of a 5% dopamine hydrochloride solution are uniformly blended according to the weight parts to obtain a glass bead solution; S02: the calcium carbonate solution and the glass bead solution are subjected to primary ball milling according to a weight ratio of 3:5, after ball milling, filtration and drying are performed, and a filling agent is obtained; S03: 5-8 parts of nano-silicon oxide liquid and 3-5 parts of filling agent are subjected to secondary ball milling treatment, after the ball milling, filtration and drying are carried out, and the filling agent based on functional improvement is obtained.

[0007] Preferably, the ball milling speed of the primary ball milling treatment is 1000-1500 r / min, and the ball milling time is 1 h; the ball milling speed of the secondary ball milling treatment is 750-850 r / min, and the ball milling time is 2 h.

[0008] Preferably, the nano-silicon oxide liquid is a solution of nano-silicon dioxide, boron nitride and sodium hexametaphosphate, and the weight ratio is (2-5):3:(7-9).

[0009] Preferably, the mass fraction of the sodium hexametaphosphate solution is 5-8%.

[0010] Preferably, the preparation method of the modified nano-titanium oxide agent is as follows: S101: nano-titanium oxide is first placed in a proton irradiation box and irradiated for 1 h, the irradiation power is 350-400 W, and after the irradiation, irradiated nano-titanium oxide is obtained; S102: silane coupling agent KH560, ethanol and 5% chitosan aqueous solution are uniformly blended according to a weight ratio of 4:7:5, and a silane coupling liquid is obtained; 3-5 parts of diatomite, 4-6 parts of kaolin and 5-9 parts of strong liquid are uniformly mixed and subjected to ball milling treatment, the ball milling speed is 1000-1500 r / min, the ball milling time is 2 h, after the ball milling, filtration and drying are carried out, and a modified additive is obtained; The modified additive and the silane coupling liquid are uniformly stirred according to a weight ratio of 3:5, and a silane coupling modified liquid is obtained. S103: the irradiated nano-titanium oxide and the silane coupling modified liquid are subjected to ultrasonic modification treatment according to a weight ratio of 5:8, after the ultrasonic modification, filtration and drying are carried out, and a modified nano-titanium oxide agent is obtained.

[0011] Preferably, the ultrasonic power of the ultrasonic modification treatment is 350-400 W, and the ultrasonic time is 1 h.

[0012] Preferably, the preparation method of the strong liquid is as follows: 2-3 parts of barium zirconate, 1-2 parts of cerium oxide and 6-9 parts of sodium silicate solution are uniformly blended, and a modified sodium silicate liquid is obtained; then 4-7 parts of silicon carbide whiskers and 3-5 parts of periclase powder are added to 5-8 parts of the modified sodium silicate liquid and uniformly blended, and a strong liquid is obtained.

[0013] Preferably, the mass fraction of the sodium silicate solution is 2-5%.

[0014] The application further provides a TPU elastic master batch produced by the production process of the TPU elastic master batch.

[0015] The application also provides a production process of the elastic adhesive liner, using the TPU elastic master batch, comprising the following steps: The TPU elastic master batch is sent into a melt blowing machine for melt blowing treatment, the melt blowing temperature is 210-230 DEG C, and the elastic adhesive liner is obtained after the melt blowing is completed.

[0016] The application also provides an elastic adhesive liner, which is produced by the production process of the elastic adhesive liner.

[0017] Compared with the prior art, the application has the following beneficial effects: 1. The TPU elastic master batch of the elastic adhesive liner uses TPU as a base body, and is blended by cooperating with a functional improvement filling agent, a modified nano titanium oxide agent as a functional additive, and adding a coupling agent KH560 and calcium stearate, and finally melt blowing to obtain the elastic adhesive liner, so that the elastic performance, air permeability and water repellency of the elastic adhesive liner are improved in coordination, and the salt corrosion resistance of the elastic adhesive liner product is significantly improved. 2. The functional improvement filling agent is treated by dispersing calcium carbonate in a sodium dodecyl benzene sulfonate solution, and then improved by cooperating with a glass bead liquid first-stage ball milling, so that the glass beads, sodium carboxymethyl cellulose and 5% mass fraction dopamine hydrochloride solution in the glass bead liquid are improved in coordination, the glass beads are supplemented to the system with calcium carbonate, the interface between the system raw materials is enhanced, the water repellent point is improved, the water repellency is enhanced, and the nano silicon dioxide, boron nitride and sodium hexametaphosphate solution in the nano silicon dioxide liquid are improved in coordination by cooperating with the nano silicon dioxide liquid second-stage ball milling, so that the high specific surface area structure of the nano silicon dioxide is cooperated with the boron nitride system, the interface connection of the functional improvement filling agent in the system is further enhanced, and the performance coordination of the system is optimized. 3. The modified nano titanium oxide agent is treated by irradiation to optimize the activity, and then treated by ultrasonic improvement by cooperating with a silane coupling modification liquid, so that the silane coupling agent KH560, ethanol and 5% mass fraction chitosan aqueous solution in the silane coupling modification liquid are improved in coordination, the hydrophobicity and interface dispersibility of the modified nano titanium oxide system are enhanced, the diatomite, kaolin and strong liquid in the silane coupling modification liquid are improved in coordination to form a base body, the air permeability of the system is enhanced, the carbon silicon whisker, periclase powder in the strong liquid are cooperated with the modified sodium silicate liquid to improve the optimization, the whisker structure of the carbon silicon whisker is cooperated with the periclase powder, and the modified sodium silicate liquid obtained by improving the whisker system through the barium zirconate, cerium oxide and sodium silicate solution is improved, so that the strong liquid is better matched with the diatomite and kaolin, and the elastic performance, air permeability and water repellency of the system are further improved in coordination, and the salt corrosion resistance is further improved. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the protection scope of the present application.

[0019] The production process of the TPU elastic master batch in the embodiment includes the following steps. Step one, the raw materials are weighed according to the weight parts: 55-60 parts of TPU, 5-8 parts of the filling agent based on functional improvement, 3-5 parts of modified nano titanium oxide agent, 2-4 parts of coupling agent KH560, and 3-5 parts of calcium stearate; Step two, the above raw materials are melt blended and extruded into granules, the rotating speed of the extruder is 150 r / min, and the extrusion temperature is 200 DEG C, to obtain the TPU elastic master batch.

[0020] The preparation method of the filling agent based on functional improvement in the embodiment is as follows: S01: calcium carbonate is added into a sodium dodecyl benzene sulfonate solution with a mass fraction of 5-8% according to a weight ratio of 3:5 and stirred uniformly to obtain a calcium carbonate liquid; 4-7 parts of glass microbeads, 2-3 parts of sodium carboxymethyl cellulose, and 5-8 parts of a dopamine hydrochloride solution with a mass fraction of 5% are uniformly blended according to the weight parts to obtain a glass microbead liquid; S02: the calcium carbonate liquid and the glass microbead liquid are subjected to primary ball milling treatment according to a weight ratio of 3:5, after the ball milling is completed, suction filtration and drying are performed to obtain the filling agent; S03: 5-8 parts of a nano silicon oxide liquid and 3-5 parts of the filling agent are subjected to secondary ball milling treatment, after the ball milling is completed, suction filtration and drying are performed to obtain the filling agent based on functional improvement.

[0021] The rotating speed of the primary ball milling treatment in the embodiment is 1000-1500 r / min, and the ball milling time is 1 h; the rotating speed of the secondary ball milling treatment is 750-850 r / min, and the ball milling time is 2 h.

[0022] The nano silicon oxide liquid in the embodiment is a nano silicon dioxide, boron nitride and sodium hexametaphosphate solution according to a weight ratio of (2-5):3:(7-9).

[0023] The mass fraction of the sodium hexametaphosphate solution in the embodiment is 5-8%.

[0024] The preparation method of the modified nano titanium oxide agent in the embodiment is as follows: S101: The nano titanium oxide is first placed in a proton irradiation box and irradiated for 1h, with an irradiation power of 350-400W. After irradiation, the irradiated nano titanium oxide is obtained; S102: The silane coupling agent KH560, ethanol and 5% chitosan aqueous solution are blended uniformly according to a weight ratio of 4:7:5 to obtain a silane coupling liquid; The 3-5 parts of diatomite, 4-6 parts of kaolin and 5-9 parts of strong liquid are uniformly mixed and ball milled at a ball milling speed of 1000-1500r / min for 2h. After ball milling, the mixture is filtered and dried to obtain a modified additive; The modified additive and the silane coupling liquid are uniformly stirred according to a weight ratio of 3:5 to obtain a silane coupling modified liquid; S103: The irradiated nano titanium oxide and the silane coupling modified liquid are ultrasonically modified according to a weight ratio of 5:8. After ultrasonic modification, the mixture is filtered and dried to obtain a modified nano titanium oxide agent.

[0025] The ultrasonic power of the ultrasonic modification in this embodiment is 350-400W, and the ultrasonic time is 1h.

[0026] The preparation method of the strong liquid in this embodiment is as follows: The 2-3 parts of barium zirconate, 1-2 parts of cerium oxide and 6-9 parts of sodium silicate solution are uniformly blended to obtain a modified sodium silicate liquid. Then, 4-7 parts of silicon carbide whiskers and 3-5 parts of periclase powder are added to 5-8 parts of the modified sodium silicate liquid and uniformly blended to obtain the strong liquid.

[0027] The mass fraction of the sodium silicate solution in this embodiment is 2-5%.

[0028] A TPU elastic master batch is produced by the production process of the TPU elastic master batch.

[0029] The production process of the elastic adhesive lining uses the TPU elastic master batch and includes the following steps: The TPU elastic master batch is fed into a melt blowing machine for melt blowing treatment at a melt blowing temperature of 210-230℃. After melt blowing, the elastic adhesive lining is obtained.

[0030] An elastic adhesive lining is produced by the production process of the elastic adhesive lining.

[0031] Embodiment 1: A production process of a TPU elastic master batch includes the following steps: Step one, the raw materials are weighed according to the weight parts: 55 parts of TPU, 5 parts of a functional improvement filler, 3 parts of a modified nano titanium oxide agent, 2 parts of a coupling agent KH560 and 3 parts of calcium stearate; Step two, melt blending, extruding and granulating the above raw materials, the rotating speed of the extruder is 150 r / min, the extruding temperature is 200℃, to obtain the TPU elastic master batch.

[0032] The preparation method of the functional improvement based filler of the embodiment is as follows: S01: calcium carbonate is added into a 5% sodium dodecyl benzene sulfonate solution according to the weight ratio of 3:5, and stirred uniformly to obtain a calcium carbonate solution; 4 parts of glass beads, 2 parts of sodium carboxymethyl cellulose and 5 parts of 5% dopamine hydrochloride solution are mixed uniformly according to weight parts to obtain a glass bead solution; S02: the calcium carbonate solution and the glass bead solution are subjected to primary ball milling treatment according to the weight ratio of 3:5, and after the ball milling is completed, the mixture is subjected to suction filtration and drying to obtain a filler; S03: 5 parts of nano silicon oxide solution and 3 parts of the filler are subjected to secondary ball milling treatment, and after the ball milling is completed, the mixture is subjected to suction filtration and drying to obtain the functional improvement based filler.

[0033] The rotating speed of the primary ball milling treatment of the embodiment is 1000 r / min, and the ball milling time is 1 h; the rotating speed of the secondary ball milling treatment is 750 r / min, and the ball milling time is 2 h.

[0034] The nano silicon oxide solution of the embodiment is a solution of nano silicon dioxide, boron nitride and sodium hexametaphosphate according to the weight ratio of 2:3:7.

[0035] The mass fraction of the sodium hexametaphosphate solution of the embodiment is 5%.

[0036] The preparation method of the modified nano titanium oxide agent of the embodiment is as follows: S101: nano titanium oxide is first placed in a proton irradiation box and irradiated for 1 h at an irradiation power of 350 W, and after the irradiation is completed, the irradiated nano titanium oxide is obtained; S102: silane coupling agent KH560, ethanol and 5% chitosan aqueous solution are mixed uniformly according to the weight ratio of 4:7:5 to obtain a silane coupling solution; 3 parts of diatomite, 4 parts of kaolin and 5 parts of strong liquid are mixed and subjected to ball milling treatment at a rotating speed of 1000 r / min for 2 h, and after the ball milling is completed, the mixture is subjected to suction filtration and drying to obtain a modified additive; The modified additive and the silane coupling solution are stirred uniformly according to the weight ratio of 3:5 to obtain a silane coupling modified solution; S103: the irradiated nano titanium oxide and the silane coupling modified solution are subjected to ultrasonic modification treatment according to the weight ratio of 5:8, and after the ultrasonic modification is completed, the mixture is subjected to suction filtration and drying to obtain the modified nano titanium oxide agent.

[0037] The ultrasonic power of the ultrasonic modification treatment of the embodiment is 350 W, and the ultrasonic time is 1 h.

[0038] The preparation method of the strong liquid of the embodiment is as follows: According to parts by weight, 2 parts of barium zirconate, 1 part of cerium oxide and 6 parts of sodium silicate solution are uniformly blended to obtain a modified sodium silicate solution; then according to parts by weight, 4 parts of silicon carbide whiskers and 3 parts of periclase powder are added to 5 parts of the modified sodium silicate solution for further blending to obtain the strong liquid.

[0039] The mass fraction of the sodium silicate solution of the embodiment is 2%.

[0040] The TPU elastic master batch of the embodiment is produced by the production process of the TPU elastic master batch.

[0041] The production process of the elastic bonded lining of the embodiment uses the TPU elastic master batch and comprises the following steps: The TPU elastic master batch is sent into a melt-blowing machine for melt-blowing treatment at a melt-blowing temperature of 210°C, and the elastic bonded lining is obtained after the melt-blowing is completed.

[0042] The elastic bonded lining of the embodiment is produced by the production process of the elastic bonded lining.

[0043] The production process of the TPU elastic master batch of the embodiment comprises the following steps: Step one, the raw materials are weighed according to parts by weight: 60 parts of TPU, 8 parts of the filling agent based on functional improvement, 5 parts of the modified nano titanium oxide agent, 4 parts of the coupling agent KH560 and 5 parts of calcium stearate; Step two, the above raw materials are melt-blended and extruded and granulated, the rotating speed of the extruder is 150 r / min and the extrusion temperature is 200°C, and the TPU elastic master batch is obtained.

[0044] The preparation method of the filling agent based on functional improvement of the embodiment is as follows: S01: calcium carbonate is added to a 8% mass fraction sodium dodecylbenzenesulfonate solution according to a weight ratio of 3:5 and stirred uniformly to obtain a calcium carbonate solution; According to parts by weight, 7 parts of glass beads, 3 parts of carboxymethyl cellulose sodium and 8 parts of a 5% mass fraction dopamine hydrochloride solution are uniformly blended to obtain a glass bead solution; S02: the calcium carbonate solution and the glass bead solution are subjected to primary ball milling treatment according to a weight ratio of 3:5, and after the ball milling is completed, suction filtration and drying are performed to obtain the filling agent; S03: 8 parts of a nano silicon oxide solution and 5 parts of the filling agent are subjected to secondary ball milling treatment, and after the ball milling is completed, suction filtration and drying are performed to obtain the filling agent based on functional improvement.

[0045] The primary ball milling treatment of the embodiment has a ball milling rotation speed of 1500r / min, and the ball milling lasts for 1h; the secondary ball milling treatment has a ball milling rotation speed of 850r / min, and the ball milling lasts for 2h.

[0046] The nano-silicon oxide liquid of the embodiment is a solution of nano-silicon dioxide, boron nitride and sodium hexametaphosphate with a weight ratio of 5:3:9.

[0047] The mass fraction of the sodium hexametaphosphate solution of the embodiment is 8%.

[0048] The preparation method of the modified nano-titanium oxide agent of the embodiment is as follows: S101: The nano-titanium oxide is first placed in a proton irradiation box for irradiation for 1h, and the irradiation power is 400W; after the irradiation, the irradiated nano-titanium oxide is obtained; S102: The silane coupling agent KH560, ethanol and a 5% mass fraction chitosan aqueous solution are uniformly blended with a weight ratio of 4:7:5 to obtain a silane coupling liquid; The 5 parts of diatomite, 6 parts of kaolin and 9 parts of strong liquid are uniformly mixed and ball milled, the ball milling rotation speed is 1500r / min, the ball milling lasts for 2h, after the ball milling, the mixture is suction filtered and dried to obtain a modified additive; The modified additive and the silane coupling liquid are uniformly stirred with a weight ratio of 3:5 to obtain a silane coupling modified liquid; S103: The irradiated nano-titanium oxide and the silane coupling modified liquid are ultrasonically modified with a weight ratio of 5:8, after the ultrasonic modification, the mixture is suction filtered and dried to obtain a modified nano-titanium oxide agent.

[0049] The ultrasonic power of the ultrasonic modification of the embodiment is 400W, and the ultrasonic modification lasts for 1h.

[0050] The preparation method of the strong liquid of the embodiment is as follows: The 3 parts of barium zirconate, 2 parts of cerium oxide and 9 parts of sodium silicate solution are uniformly blended to obtain a modified sodium silicate liquid; then 7 parts of silicon carbide whiskers and 5 parts of periclase powder are added into 8 parts of the modified sodium silicate liquid for further uniform blending to obtain the strong liquid.

[0051] The mass fraction of the sodium silicate solution of the embodiment is 5%.

[0052] The TPU elastic master batch of the embodiment is produced by the production process of the TPU elastic master batch.

[0053] The production process of the elastic bonded lining of the embodiment uses the TPU elastic master batch, and includes the following steps: The TPU elastic master batch is sent into a melt-blowing machine for melt-blowing treatment, the melt-blowing temperature is 230℃, after the melt-blowing, the elastic bonded lining is obtained.

[0054] The elastic adhesive backing of the embodiment is produced by the production process of the elastic adhesive backing.

[0055] Embodiment 3: A production process of a TPU elastic master batch, comprising the following steps: Step one, the raw materials are weighed according to the weight parts: 57.5 parts of TPU, 6.5 parts of functional improvement based filling agent, 4 parts of modified nano titanium oxide agent, 3 parts of coupling agent KH560, 4 parts of calcium stearate; Step two, melt blending and extruding granulation of the above raw materials, the rotating speed of the extruder is 150 r / min, the extrusion temperature is 200℃, and the TPU elastic master batch is obtained.

[0056] The preparation method of the functional improvement based filling agent of the embodiment is: S01: calcium carbonate is added to a 6.5% sodium dodecylbenzenesulfonate solution according to a weight ratio of 3:5 and stirred uniformly to obtain a calcium carbonate liquid; 5.5 parts of glass beads, 2.5 parts of sodium carboxymethyl cellulose, and 6.5 parts of 5% dopamine hydrochloride solution are blended uniformly according to the weight parts to obtain a glass bead liquid; S02: the calcium carbonate liquid and the glass bead liquid are subjected to primary ball milling treatment according to a weight ratio of 3:5, after the ball milling is completed, suction filtration and drying are performed to obtain a filling agent; S03: 6.5 parts of nano silicon oxide liquid and 4 parts of filling agent are subjected to secondary ball milling treatment, after the ball milling is completed, suction filtration and drying are performed to obtain the functional improvement based filling agent.

[0057] The primary ball milling treatment of the embodiment has a ball milling rotating speed of 1250 r / min and a ball milling time of 1 h; the secondary ball milling treatment has a ball milling rotating speed of 800 r / min and a ball milling time of 2 h.

[0058] The nano silicon oxide liquid of the embodiment is a nano silicon dioxide, boron nitride and sodium hexametaphosphate solution according to a weight ratio of 3.5:3:8.

[0059] The mass fraction of the sodium hexametaphosphate solution of the embodiment is 6.5%.

[0060] The preparation method of the modified nano titanium oxide agent of the embodiment is: S101: nano titanium oxide is first placed in a proton irradiation box and irradiated for 1 h, the irradiation power is 375 W, after the irradiation is completed, the irradiated nano titanium oxide is obtained; S102: silane coupling agent KH560, ethanol and 5% chitosan aqueous solution are blended uniformly according to a weight ratio of 4:7:5 to obtain a silane coupling liquid; 4 parts of diatomite, 5 parts of kaolin and 7 parts of strong liquid were mixed and ball milled, the ball milling speed was 1250 r / min, the ball milling time was 2 h, after the ball milling, the mixture was filtered and dried to obtain a modified additive; The modified additive and the silane coupling liquid were stirred uniformly according to a weight ratio of 3:5 to obtain a silane coupling modified liquid. S103: The irradiated nano titanium oxide and the silane coupling modified liquid were ultrasonically modified according to a weight ratio of 5:8, after the ultrasonic modification, the mixture was filtered and dried to obtain a modified nano titanium oxide agent.

[0061] The ultrasonic power of the ultrasonic modification in the embodiment was 375 W, and the ultrasonic time was 1 h.

[0062] The preparation method of the strong liquid in the embodiment was as follows: 2.5 parts of barium zirconate, 1.5 parts of cerium oxide and 7 parts of sodium silicate solution were uniformly blended to obtain a modified sodium silicate liquid; then 5.5 parts of silicon carbide whisker and 4 parts of periclase powder were added into 6.5 parts of the modified sodium silicate liquid to continue to blend sufficiently to obtain the strong liquid.

[0063] The mass fraction of the sodium silicate solution in the embodiment was 3.5%.

[0064] The TPU elastic master batch in the embodiment was produced by the production process of the TPU elastic master batch.

[0065] The production process of the elastic bonded lining in the embodiment used the TPU elastic master batch and included the following steps: The TPU elastic master batch was sent into a melt blowing machine for melt blowing treatment, the melt blowing temperature was 220°C, and after the melt blowing, an elastic bonded lining was obtained.

[0066] The elastic bonded lining in the embodiment was produced by the production process of the elastic bonded lining.

[0067] Comparative Example 1: Different from Example 3 was that no functional improvement based filler was added.

[0068] Comparative Example 2: Different from Example 3 was that no filler was added in the preparation of the functional improvement based filler.

[0069] Comparative Example 3: Different from Example 3 was that no calcium carbonate liquid was added in the filler.

[0070] Comparative Example 4: Different from Example 3 was that no glass bead liquid was added in the filler.

[0071] Comparative Example 5: The difference between Example 3 is that the nano-silicon oxide liquid is not added in the preparation of the functional modified nano-titanium oxide agent.

[0072] Comparative Example 6: The difference between Example 3 is that the modified nano-titanium oxide agent is not added.

[0073] Comparative Example 7: The difference between Example 3 is that the irradiated nano-titanium oxide is not added in the preparation of the modified nano-titanium oxide agent.

[0074] Comparative Example 8: The difference between Example 3 is that the silane coupling modification liquid is not added in the preparation of the modified nano-titanium oxide agent.

[0075] Comparative Example 9: The difference between Example 3 is that the modified additive is not added in the silane coupling modification liquid.

[0076] Comparative Example 10: The difference between Example 3 is that the diatomite and kaolin are not added in the modified additive.

[0077] Comparative Example 11: The difference between Example 3 is that the strong liquid is not added in the modified additive.

[0078] Comparative Example 12: The difference between Example 3 is that the silicon carbide whisker and periclase powder are not added in the strong liquid.

[0079] Comparative Example 13: The difference between Example 3 is that the barium zirconate and cerium oxide are not added in the strong liquid.

[0080] The elastic performance, air permeability and water repellency of the elastic adhesive lining products of Examples 1-3 and Comparative Examples 1-13 are tested under normal conditions and salt corrosion resistant conditions, and the salt corrosion resistant conditions are that the elastic adhesive lining products are placed in a 5% sodium chloride salt spray for 48 hours, and the test results are shown in Table 1.

[0081] Table 1: Performance test results of the elastic adhesive lining products of Examples 1-3 and Comparative Examples 1-13: From Examples 1-3 and Comparative Examples 1-13, it can be seen that the elasticity, air permeability and contact angle of the elastic adhesive lining product of Example 3 can be improved in a coordinated manner, the elasticity, air permeability and water repellency of the elastic adhesive lining product are significantly improved, and the performance stability of the elastic adhesive lining product under salt spray resistant conditions is significantly improved. The performance of the product is significantly deteriorated when one of the functional modified filler and the modified nano-titanium oxide agent is not added in the TPU elastic master batch, and the performance of the product is most significantly improved when both are used in a synergistic manner. Based on the functional improvement of the filling agent, the filling agent is not added in the preparation, the calcium carbonate liquid is not added in the filling agent, the glass bead liquid is not added in the filling agent, the nano silicon oxide liquid is not added in the preparation of the filling agent based on the functional improvement, and the performance of the product has a different degree of deterioration trend, and the filling agent based on the functional improvement obtained by the specific method has the most significant performance effect on the product. In the preparation of the modified nano titanium oxide agent, the irradiated nano titanium oxide is not added, the silane coupling modification liquid is not added in the preparation of the modified nano titanium oxide agent, the modified additive is not added in the silane coupling modification liquid, the diatomite and kaolin are not added in the modified additive, the strong liquid is not added in the modified additive, the silicon carbide whisker and periclase powder are not added in the strong liquid, the barium zirconate and cerium oxide are not added in the strong liquid, and the performance of the product also appears a different degree of deterioration trend. The modified nano titanium oxide agent prepared by the silane coupling modification liquid and the irradiated nano titanium oxide obtained by the specific method of the application has the most significant performance effect on the product. At the same time, the strong liquid prepared by the specific method of the application has the most obvious performance effect on the product, and the modified additive obtained by the specific strong liquid and diatomite and kaolin has the most significant performance effect on the product, and the effect of other methods instead is not as obvious as that of the application.

[0082] For those skilled in the art, it is obvious that the present application is not limited to the details of the above exemplary embodiments, and the present application can be realized in other specific forms without departing from the spirit or essential characteristics of the present application. Therefore, the embodiments should be regarded as exemplary and non-limiting, and the scope of the present application is defined by the appended claims rather than the above description, and all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be included in the present application.

[0083] In addition, it should be understood that although the present specification is described in terms of embodiments, each embodiment does not contain only one independent technical solution, and the description manner of the specification is only for clarity, and those skilled in the art should regard the specification as a whole, and the technical solutions in each embodiment can also be combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. The production process of TPU elastic masterbatch, characterized in that, Includes the following steps: Step 1: Weigh the raw materials according to their weight proportions: 55-60 parts TPU, 5-8 parts functionally improved filler, 3-5 parts modified nano-titanium oxide agent, 2-4 parts coupling agent KH560, and 3-5 parts calcium stearate; The preparation method of the functionally improved filler is as follows: S01: Add calcium carbonate to a sodium dodecylbenzenesulfonate solution with a mass fraction of 5-8% at a weight ratio of 3:5 and stir until homogeneous to obtain calcium carbonate solution; 4-7 parts by weight of glass microspheres, 2-3 parts by weight of sodium carboxymethyl cellulose, and 5-8 parts by weight of 5% dopamine hydrochloride solution are mixed evenly to obtain glass microsphere solution. S02: Calcium carbonate solution and glass microsphere solution are subjected to primary ball milling at a weight ratio of 3:

5. After ball milling, the solution is filtered and dried to obtain the filler. S03: 5-8 parts by weight of nano-silica liquid and 3-5 parts by weight of filler are subjected to two-stage ball milling. After ball milling, the mixture is filtered and dried to obtain filler based on functional improvement. Step 2: Melt and blend the above raw materials, then extrude and granulate them. The extruder speed is 150 r / min and the extrusion temperature is 200℃ to obtain TPU elastic masterbatch.

2. The production process of TPU elastic masterbatch according to claim 1, characterized in that, The ball milling process for the first stage is carried out at a speed of 1000-1500 r / min for 1 hour; the ball milling process for the second stage is carried out at a speed of 750-850 r / min for 2 hours.

3. The production process of TPU elastic masterbatch according to claim 1, characterized in that, The nano-silica solution is composed of nano-silica, boron nitride, and sodium hexametaphosphate solution in a weight ratio of (2-5):3:(7-9), and the sodium hexametaphosphate solution has a mass fraction of 5-8%.

4. The production process of TPU elastic masterbatch according to claim 1, characterized in that, The preparation method of the modified nano-titanium oxide agent is as follows: S101: Place the nano-titanium oxide in a proton irradiation chamber for 1 hour with an irradiation power of 350-400W. After irradiation, the irradiated nano-titanium oxide is obtained. S102: Silane coupling agent KH560, ethanol and 5% (w / w) chitosan aqueous solution are mixed evenly in a weight ratio of 4:7:5 to obtain silane coupling solution; Mix 3-5 parts by weight of diatomaceous earth, 4-6 parts by weight of kaolin and 5-9 parts by weight of high-efficiency liquid and ball mill them at a speed of 1000-1500 r / min for 2 hours. After ball milling, filter and dry to obtain the modified additive. The modified additive and silane coupling solution were stirred evenly at a weight ratio of 3:5 to obtain the silane coupling modified solution. S103: Irradiated nano-titanium oxide and silane coupling modification liquid are ultrasonically modified at a weight ratio of 5:

8. After ultrasonic treatment, the mixture is filtered and dried to obtain modified nano-titanium oxide agent.

5. The production process of TPU elastic masterbatch according to claim 4, characterized in that, The ultrasonic power for the ultrasonic modification treatment is 350-400W, and the ultrasonic treatment lasts for 1 hour.

6. The production process of TPU elastic masterbatch according to claim 4, characterized in that, The preparation method of the high-efficiency liquid is as follows: By weight, 2-3 parts of barium zirconate, 1-2 parts of cerium oxide and 6-9 parts of sodium silicate solution with a mass fraction of 2-5% are mixed evenly to obtain modified sodium silicate solution. Add 4-7 parts by weight of silicon carbide whiskers and 3-5 parts by weight of periclase powder to 5-8 parts of modified sodium silicate solution and continue to mix thoroughly to obtain a high-efficiency solution.

7. TPU elastic masterbatch, produced by the manufacturing process of TPU elastic masterbatch as described in any one of claims 1 to 6.

8. A manufacturing process for an elastic adhesive liner, using the TPU elastic masterbatch as described in claim 7, characterized in that, Includes the following steps: The TPU elastic masterbatch is fed into a meltblown machine for meltblown treatment at a temperature of 210-230℃. After meltblown treatment, an elastic adhesive liner is obtained.

9. An elastic adhesive liner, produced by the manufacturing process of the elastic adhesive liner as described in claim 8.

Citation Information

Patent Citations

  • Flame-retardant TPU (thermoplastic polyurethane) film and preparation method thereof

    CN119463460A

  • Glass fiber reinforced halogen-free flame-retardant PBT / PC (polybutylene terephthalate / polycarbonate) alloy material with high dimensional stability

    CN119708777A

  • Preparation process of EVA (Ethylene Vinyl Acetate) modified particles, EVA modified particles and application of EVA modified particles

    CN119931193A

  • High-toughness regenerated ABS (Acrylonitrile Butadiene Styrene) composite material and preparation method thereof

    CN120230369A

  • Preparation method for environment-friendly natural bamboo fiber-modified pe composite material and product, and use

    WO2024208284A1